2015
DOI: 10.1007/s10875-015-0214-9
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Clinical Phenotype of 26 Patients with Chronic Mucocutaneous Candidiasis due to Gain-of-Function Mutations in STAT1

Abstract: PurposeGain-of-function (GOF) mutations in the signal transducer and activator of transcription 1 (STAT1) result in unbalanced STAT signaling and cause immune dysregulation and immunodeficiency. The latter is often characterized by the susceptibility to recurrent Candida infections, resulting in the clinical picture of chronic mucocutaneous candidiasis (CMC). This study aims to assess the frequency of GOF STAT1 mutations in a large international cohort of CMC patients.MethodsSTAT1 was sequenced in genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 45 publications
3
142
0
2
Order By: Relevance
“…P2 and P4 were also treated for suspected pulmonary tuberculosis and tuberculous meningitis, respectively, without microbiological confirmation. None of the other clinical manifestations previously reported in patients with GOF STAT1 mutations, such as autoimmune endocrinopathy, aneurysms, or mucosal carcinomas, were detected (16,17,23,37,51). Detailed phenotyping of lymphocyte subsets was performed for patients from kindreds D, E, and H and revealed no abnormality (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…P2 and P4 were also treated for suspected pulmonary tuberculosis and tuberculous meningitis, respectively, without microbiological confirmation. None of the other clinical manifestations previously reported in patients with GOF STAT1 mutations, such as autoimmune endocrinopathy, aneurysms, or mucosal carcinomas, were detected (16,17,23,37,51). Detailed phenotyping of lymphocyte subsets was performed for patients from kindreds D, E, and H and revealed no abnormality (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In patients with STAT1 GOF mutations, CMC results, at least partly, from impairment of the development and/or survival of IL-17A/F-producing T cells, the underlying mechanisms of which remain unknown (28,52). Patients with these mutations, who had long been known to be prone to thyroid autoimmunity, were recently found to display other infectious and autoimmune phenotypes (16,17,23,37,51). Another genetic etiology of syndromic CMCD has recently been described, with AR retinoic acid-related orphan receptors γ (ROR-γ/γT) deficiency in three kindreds with CMC and severe mycobacterial disease (53).…”
Section: Significancementioning
confidence: 99%
“…This is consistent with previous clinical observations that most reported disease-causing mutations in CCD/DBD are GOF and are associated with CMC. 4, 15, 16, 22, 36 In contrast, only two AD MSMD-related LOF mutations, E320Q and Q463H, both in DBD, have yet been reported in those domains. 10 The alanine-scanning assay revealed that four of 176 alanine substituents (E157A, T224A, G250A, and Q311A) in CCD were LOF.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic mucocutaneous candidiasis is a clinical syndrome characterized by recurrent infections of mucus membranes and skin with Candida species. A majority of these patients have been shown to have gain-of-function mutations in STAT1, which promote type 1 immune responses and repress type 17 responses, predisposing individuals to infection with fungal diseases (5458). Additionally, loss-of-function mutations in STAT1 have also been identified that confer significant susceptibility to viral and mycobacterial infections (59).…”
Section: Discussionmentioning
confidence: 99%